GAMBARAN ANGKA LEMPENG TOTAL DAN IDENTIFIKASI Escherichia coli PADA BAKSO AYAM YANG DIJUAL DI DESA SANUR KAUH DENPASAR SELATAN - I Gede Sudarmanto (Meditory : The Journal of Medical Laboratory, 2021)
ABSTRACTIntroduction: Chicken meatballs are a typical Indonesian processed meat food made from a mixture of chicken meat, tapioca flour, and spices. Chicken meatballs are one of the favorite foods of the society, but several studies on meatballs still show the result that meatballs unqualified in health.Aims: The aim of this study was to determine the quality of bacteriology of chicken meatball which are sold in Sanur Kauh Village. The parameters analyze were total plate count and identification of Escherichia coli bacteria. Methods:This research used description study with laboratory examination conducted at Panureksa Utama Laboratory. Total sample that taken in this study were 12 samples of chicken meatball. The sampling technique is using saturated sampling. Results: Based on total plate count examination, it was found from 12 samples chicken meetballs that 3 samples (25%) unqualified and 9 samples (75%) qualified according to SNI No. 01-3818:2014 about Bakso Daging. The results of identification of Escherichia coli bacteria was found that 1 sample chicken meatball (8,3%) unqualified and 11 samples (91.7%) qualified according to Permenkes No. 1096/MENKES/PER/VI/2011.Discusion: Based on the results, it can be conclude was the most of chicken meatballs was qualified in health. The sellers must be attentive about sanitation and personal hygiene during processing of chicken meatballs.Keywords: chicken meatballs, quality of bacteriology, total plate count, Escherichia coli.